Relationship Of Age, Access To Information And Education Level With Knowledge About Reproductive Health In Elementary School Teachers - Anisa Hasna Zakiyya; Tanjung Anitasari Indah Kusumaningrum (KESMAS UWIGAMA: Jurnal Kesehatan Masyarakat, 2022)
Background: Elementary school teachers have an important role in providing information about reproductive health for students and work in preventing sexual violence against children. Objective : This study aims to analyze whether there is a relationship between age, access to information, and level of education with knowledge about reproductive health in elementary school teachers (SD). Research Methods: This study used an analytical observational research method with a cross-sectional approach. This research was conducted in an elementary school (SD) in the Karangnongko sub-district with 192 teachers as respondents. Retrieval of respondents using Exhaustive Sampling and data analysis using Chi-Square. Results: The results showed that there was no relationship between age (p>0,328), access to information (p>0,518) and education level (p>0,341) with knowledge about reproductive health in elementary school teachers (SD). Conclusion : There is no relationship between age, access to information and education with knowledge about reproductive health in elementary school teachers (SD). Suggestion: Teachers are expected to be able to provide instructions for teachers in teaching. Keywords : age, access to information, education level, knowledge, reproductive health, elementary school (SD) teachers.